The Incas - Pease G. Y., Franklin; Tegel, Simeon (Pontificia Universidad Católica del Perú. Fondo Editorial, 2011)
In The Incas, Peruvian historian Franklin Pease G. Y. explores all aspects of life in the Tawantinsuyu, the great Inca empire that stretched for thousands of miles along the Andes of modernday Bolivia, Chile, Ecuadro and Peru. Pease does so by reexamining the sources of most of our knowledge of this complex society, the "chronocles" written during and after the Spanish conquest by a disparate group of soldiers, priests, colonial administrators ands the descendants of this protagonists, often themselves of mixed Andean-Spanish blood. This account opens a window into the Inca universe, vividly explaining everything from the Inca polity and economic structures to its agriculture, transportation infrastructure, creation myths and religious beliefs. It also takes great care to avoid the common historioraphical error of projecting onto the Incas, arguably the last great civilization to have existed without contac with the "Old World" western ways of seeing and imagining the universe.
176 p.
Keywords: Incas; https://purl.org/pe-repo/ocde/ford#6.01.01